Micropaleontological Analysis of Rocks of Mbakwah and Environs, Gboko, Southeast Nigeria (Global Journal of Science Frontier Research, 2020)
Micropaleontological analyses of rock samples from outcrops and hand-dug wells in Gboko and its environs were carried out to better understand the geology of the area, properly delineate the various lithologies and infer the ages of the rocks. Detailed geologic mapping, micropaleontologic and petrographic methods were applied. Micropaleontological analysis involved washing and viewing of shale samples under microscope for the identification of the microfossils. The area is underlain by black shale inter-bedded with calcareous sandstone and carbonaceous limestone beds. Results of micropaleontological analysis yielded foraminifers and ostracods ranging from Cenomanian to Coniacian. Ovocytherideasymmetrica and Ovocytheridea-reniformisranges from Cenomenian to Coniacian, while Ovocytherideaashakaensis and Clithocytheridea-senegaliare indices of Turonian age. Foraminiferal analysis reveals the occurrence of benthic and planktonic index forms including Ammobaculitesjessensis, Ammobaculitesbenuensis, Whiteinell-abaltica and Heterohelixreussi. The dominant arenaceous benthic foraminifers and the smooth ostracods suggests a shallow marginal marine brackish water environment.